Answer:
y =
![(b)/(1-m)](https://img.qammunity.org/2022/formulas/mathematics/college/l84mj420gkjteaypfqommrpy7e3hqh8vcs.png)
Explanation:
In order to get y by itself, we need to pull y out of 1 and m on the right side.
b = y(1 - m) since y(1 - m) is the same as y - my.
Once we have pulled y out of 1 and m, we can divide both sides by 1 - m
=
![(y(1 - m))/(1 - m)](https://img.qammunity.org/2022/formulas/mathematics/college/96r0uf7hckl9fqa8sen43ods00n3rpaiou.png)
We can cancel out the 1 - m on the right side since (1 - m) / (1 - m) = 1
Finally we get our answer:
= y
This is the same as y =
![(b)/(1-m)](https://img.qammunity.org/2022/formulas/mathematics/college/l84mj420gkjteaypfqommrpy7e3hqh8vcs.png)